Elementary School Students’ Table Tennis Game Knowledge Level - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Saleh, M Sahib (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research is a type of descriptive research. This research aims to find out the level of Knowledge of the Table Tennis Game of Class V Students of SD Negeri III Karuwisi. The population was all Class V students at SD Negeri III Karuwisi. The research sample used was 50 students. The sample determination technique is random selection by lottery (Simple Random Sampling). The data analysis technique used is descriptive analysis. The research results show that; The level of table tennis for Class V students at SD Negeri III Karuwisi is very high